Can advertising creativity affect product perceptions and retailer evaluations? - Modig, Erik and Rosengren, Sara (Journal of Product & Brand Management, 2014)
Purpose – This paper aims to investigate the impact of advertising creativity on consumer perceptions of product quality, value, retailer brand attitude and purchase intention. Design/methodology/approach – Two experimental studies were conducted. Study 1 shows the impact of creativity (high/low) for two product categories (mineral water and chewing gum) and one known retailer. The findings are replicated and extended in Study 2 for four categories (mineral water, chewing gum, batteries and detergent) and two known retailers. Findings – The results show that advertising creativity positively signals perceived product quality, which increases perceived value. These effects fully mediate a positive impact on retailer brand attitude and purchase intentions. The positive effect of advertising creativity on perceived product quality is mediated by perceived advertisement effort. Practical implications – This study introduces advertising creativity as a way for retailers to increase perceived product quality and value. The results show that advertising creativity increases perceived effort on behalf of the sender, which positively influences purchase intentions. Originality/value – The current study shows that advertising creativity can work as a signal of product quality, which has positive effects for retailers.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTEwOC9qcGJtLTA2LTIwMTQtMDY1MQ